(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The author proposes that the original name of the Garonne River was Garunda, preserved to some extent in the modern name for its estuary, Gironde. He makes also some morpho observations about the prehistoric Hydronymy of Europe.